Rāgs Around the Clock: A Handbook for North Indian Classical Music, with Online Recordings in the Khayāl Style - Clarke, David (Open Book Publishers, 2024)
Rāgs Around the Clock is a rich and vibrant compendium for the discovery and study of North Indian classical music. The theory and practice of rāg are explored through two interlinked resources: a handbook of essays and analyses offering technical, historical, cultural and aesthetic perspectives; and two online albums – Rāg samay cakra and Twilight Rāgs from North India – featuring khayāl singer Vijay Rajput and accompanists. Extracts from the albums are also embedded into the text to enhance learning and understanding. Each rāg is accompanied by a description of its chief characteristics and technical features, a notation of the song (bandiś) on which the performance is based, and a transliteration and translation of the song text. Distinctively, Rāg samay cakra also includes spoken renditions of each of the texts, helping non-Hindavi speakers to achieve the correct pronunciation. Sharing insights from both theory and practice, this collection draws on recent scholarship while also showcasing the vocal idiom – the gāyakī – of Vijay Rajput, a disciple of the late Pandit Bhimsen Joshi. It offers invaluable reading for students and researchers of Indian classical music, world music and ethnomusicology, and a rich repository for teacher and student practitioners of the khayāl vocal style. The combination of an aural and written exploration of rāg will appeal to anyone drawn to this form of music – whether newcomer, student (śiṣyā) or aficionado (rasika).